Tradition and Modernism in the Works of Wilhelm Georg Berger; Sonata for Viola and Cello Op. 18 - Leona VARVARICHI (Studia Universitatis Babeş-Bolyai. Musica, 2024)
This study aims to reveal the blend of the traditional with the modern in the works of Wilhelm Georg Berger, based on the analysis of the Sonata for Viola and Cello Op. 18 composed in 1962. His work covers more than 50 years, a period in which his style transformed so that Berger composes applying principles formulated through the assiduous research of the musical phenomena, being familiar, in detail, with the old as well as the new. In the first part of the analysis, I shall briefly present aspects of his multidisciplinary personality, starting from the cultural background and context in which Berger created. In the second part, I shall analyze the Sonata for Viola and Cello Op. 18, from which I have selected the elements I have considered the most relevant in highlighting the blending between traditional and modern. The aspects are selected through the lens of formal, harmonic, modal, rhythmic, or aesthetic points of view.